النمذجة المفاهيمية للغة: إسهامات اللسانيات المعرفية في سياق العلوم المعرفية: Conceptual Language Modeling: Cognitive linguistics contributions in the context of cognitive sciences - Bernoussi, Hasbiya Taifi (SIBAWAYH Arabic Language and Education, 2020)
Cognitive science is concerned with describingthe preparations and the fundamental abilities of human mind, explaining and standardizing them: language rationalization, awareness, kinetic coordination and planning, curricula and concepts. In spite of their participation in the cognitive subject that makes them engage intentionally in the field of cognitive sciences, they are able to build for themselves, cross-pollination of several specialties, a system of advanced scientific models. In this article, we will show how the conceptual models of language emerge in the context of cognitive sciences and the way in which they evolve through the multiplicity of sciences contributing to their structure and the development of this epistemological approach, including the concept of language processing (perception and achievement) and the concept of memory as a crossing bridge between them, from models on a multidisciplinary background, to describe the effectiveness of the self in its engagement with the subjects of the surrounding world, and also to clarify the nature of the mental entities that are built and the forms according to which they are organized. We analyzed the subject from a cognitive linguistics perspective, with the use of cognitive disciplines that demonstrate other aspects.